Status of Some Trace Elementsin Idiopathic and Ischemic Cardiomyopathy and Coronary Artery Disease: Echocardiographic Correlation - Saleh, Basil O.; Majid, Ali Y.; Hussein, Waleed K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background:The most principal mechanisms of cardiomyopathies are;high preload and afterload and low myocardial contractility, imbalance of trace elements may cause myocardial metabolic dysfunction and may have a role in aetiology of cardiomyopathy, particulary in IDC. Trace elements are being increasingly recognized as essential mediators of the development and progression of heart diseases. Methods: Study design Multi case-control study and single center estimation of trace elements concentrations in a number of volunteer settings this study was conducted in the Department of Cardiology, Ibn Albitar Hospital, and in the Physiological Chemistry Department of the College of Medicine, Baghdad University, from June 2005 to July 2006. Subjects Twenty-five patients with IDC, 15 patients with ICM, 16 patients with coronary artery disease(CAD) who have normal LV function, and seventeen healthy individuals as controls were included in this study. Investigations included serum estimation of zinc (Zn), copper (Cu), and magnesium (Mg) concentrations in these groups of patients and controls. Results: The mean (±SD) value of serum zinc was significantly decreased in CAD patients compared with controls (P< 0.003). Serum Cu values (mean±SD) were significantly higher in IDC, ICM and CAD groups than in controls (P< 0.0001, P< 0.002, and P< 0.007, respectively). Serum Mg (mean±SD) value was significantly decreased in ICM patients compared to controls (P<0.007). Furthermore, there was a significant positive correlation between serum Mg levels and the values of LVEF % in IDC patients (r=0.522, P< 0.007). Conclusion: This study confirmed that heart failure (IDC and ICM) and CAD are associated with serum trace elements (Zn, C u, and Mg) abnormalities.